Limited penetration of cobalt and chromium ions into the cerebrospinal fluid following metal on metal arthroplasty: a cross-sectional analysis. (2nd April 2020) - Harrison-Brown, Meredith; Scholes, Corey; Field, Clarice; McQuilty, Robert; Farah, Sami B.; Nizam, Ikram; Kerr, Dennis; Kohan, Lawrence
Abstract: Background: The purpose of this study was to determine the concentration of cobalt (Co) and chromium (Cr) ions in synovial fluid, blood plasma and cerebrospinal fluid (CSF) of patients with metal-on-metal (MoM) implants, and to assess the relationship between implant history and patient characteristics with ion concentrations in CSF. Methods: An observational, non-randomised cross-sectional study was conducted with patients presenting to a single surgeon for treatment of degenerative conditions of the hip and knee. Blood and fluid samples were collected intraoperatively and analysed for proteins and trace elements. Results: Overall, the presence of an implant was associated with significantly higher Co and Cr concentrations in plasma (controls 5–115 nmol/L Co, 5–232 nmol/L Cr; well-functioning implant recipients 5–469 nmol/L Co, 5–608 nmol/L Cr; hip revisions 6–546 nmol/L Co, 5–573 nmol/L Cr), and for Cr concentrations in CSF (controls 5–24 nmol/L; well-functioning implant recipients 6–36 nmol/L, hip revisions 7–32 nmol/L). In absolute terms, <1% of the levels observed in the joint fluid and <15% of plasma metals appeared in the CSF. Multivariable regression models suggested different transfer mechanisms of Co and Cr to the CSF, with the presence of an implant not associated with ion levels. Conclusion: The presence of MoM implants is associated with significantly higher plasma levels of Co and Cr but not CSF levels, and the CSF/plasma ratio appears to be influenced by the plasma concentration in a nonlinear fashion. Co and Cr may be transferred to the CSF by different mechanisms, and their concentrations appears dependent on other factors yet to be identified. Although higher levels of plasma ions are associated with above average CSF metal concentrations, the thresholds for neurotoxicity remain unclear and require further study.